Effectiveness of human albumin solution in the treatment of patients with cirrhosis (Annals of Medical Research, 2022)
Aim: Human serum albumin is synthesized in the liver and is the main plasma protein responsible for plasma oncotic pressure. Studies on the use of Human albumin solution (HAS) in patients with cirrhosis, for prevention of cirrhosis complications or for treatment are ongoing. The beneficial role of albumin beyond volume expansion is an evolving field, and further research is needed to understand the role of albumin in modulating biological functions and disease processes, particularly in liver disease and sepsis, but also in other diseases with albumin dysfunction.Materials and Methods: We investigated the effectiveness of HAS through the patients with cirrhosis who received 3 consecutive days (2x1 per day) 190-210 g / L protein were retrospectively analyzed.Results: Albumin infusion was found to be beneficial for serum albumin levels in the patient with high Child-Pugh scores.Conclusions: The complications of cirrhosis can be reduced, particularly in patients awaiting transplantation, by support with HAS treatment.
Keywords: Cirrhosis; Albumin treatment; Liver transplant; Ascites